2014
DOI: 10.1075/eurosla.14.04sna
|View full text |Cite
|
Sign up to set email alerts
|

Aspect in L2 English

Abstract: Our study reports on data collected on three separate occasions over a period of 12 months from four Japanese child returnees who had lived in the U.S. between 8 and 12 years before returning to Japan. Their English proficiency was assessed by TOEIC and C-test scores, and they were each asked to complete an Acceptability Judgment Task (AJT). Results show very little change across Test sessions 1, 2 and 3. Initially, we expected to find differences over the course of 12 months as the returnees' exposure and dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…So far, the most investigated languages in the context of returnees are German (based on returnees from Germany or Switzerland to Turkey, Daller, , and Kuhberg, , and to Portugal, Flores, , , ); and English (based on returnees from the United States to Japan, e.g., Hansen, ; Kubota, ; Snape, Matthews, Hirakawa, Hirakawa, & Yosoi, ; Taura, ; Yoshitomi, , and to Berman & Olshtain, ; Olshtain, ; Seliger, ). These studies differ substantially regarding not only the methods of data collection, but also the analyzed linguistic domains and the participants’ bilingual profile.…”
Section: Background To the Studymentioning
confidence: 99%
“…So far, the most investigated languages in the context of returnees are German (based on returnees from Germany or Switzerland to Turkey, Daller, , and Kuhberg, , and to Portugal, Flores, , , ); and English (based on returnees from the United States to Japan, e.g., Hansen, ; Kubota, ; Snape, Matthews, Hirakawa, Hirakawa, & Yosoi, ; Taura, ; Yoshitomi, , and to Berman & Olshtain, ; Olshtain, ; Seliger, ). These studies differ substantially regarding not only the methods of data collection, but also the analyzed linguistic domains and the participants’ bilingual profile.…”
Section: Background To the Studymentioning
confidence: 99%
“…A further variable that distinguishes the different returnee populations studied so far is the language of the host country. Many studies report on bilingual returnee children who return from English-dominant environments (Berman & Olshtain, 1983;Yoshitomi, 1999;Taura, 2008;Tomiyama, 2008;Snape et al, 2014;Kubota et al, 2020a) and thus speak English as their L2, while bilingual returnees in the European context often speak other European languages (such as German or French) as their 2L1/L2. Given that English is a high-prestige language and is taught as one of the main subjects in schools worldwide, it is not surprising that the Japanese families make greater effort and are highly motivated in maintaining their children's English ability.…”
Section: Who Are Returnees?mentioning
confidence: 99%
“…Most L2 attrition studies involving child returnees are case studies with a reduced number of participants (see Flores, 2019 for an overview; an exception are Kubota's studies on Japanese returnees). Similarly to the two L3 attrition studies, several L2 attrition studies on child returnees present longitudinal analyses of the attrition trajectory in the L2 from the moment of return until some months (and no longer than two or three years) later (Kuhberg, 1992;Reetz-Kurashige, 1999;Tomiyama, 1999Tomiyama, , 2000Yoshitomi, 1999;Snape et al, 2014;Flores, 2015). They focus on lexical knowledge, morphosyntax, semantics or, more recently, processing costs and cognitive function (Kubota, 2019;Kubota et al, 2020aKubota et al, , 2020bKubota et al, , 2020c.…”
Section: Who Are Returnees?mentioning
confidence: 99%
“…Tomiyama concluded that the inappropriate use of the s-genitive is an indicator of L1 CLI, since the genitive form in Japanese resembles the linear order in the s-genitive in English. Moreover, studies from Yoshitomi (2007); Snape et al (2014) reveal that aspectual domain in L2 English showed some signs of attrition after 8−12 months of returning to Japan.…”
Section: Language Dominancementioning
confidence: 99%